1990
DOI: 10.1017/s0021859600074037
|View full text |Cite
|
Sign up to set email alerts
|

Replacement of palm oil by thevetia oil in broiler chick diets

Abstract: S U M M A R YThe effects of replacing 0, 25, 50 or 100 % of dietary palm oil (5 %) with oil of Thevetia peruviana was investigated using broiler chicks 0-3 weeks old.Increasing the content of thevetia oil in the diet reduced average daily feed intake and weight gain ( P < 0 0 5 ) and decreased protein and fibre retention (P < 005) and fat retention (P < 001). However, there was no significant effect on feed: gain ratio or mortality rate. It is concluded that there is a need for further processing of thevetia o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…The poor feed: gain ratio as dietary thevetia cake increased seems to confirm this assertion. Atteh et al (1990) previously reported similar trends in the performance of broiler chicks when oil extracted from thevetia seed was used as a substitute for palm oil in broiler diets.…”
Section: Chick Performancesupporting
confidence: 55%
“…The poor feed: gain ratio as dietary thevetia cake increased seems to confirm this assertion. Atteh et al (1990) previously reported similar trends in the performance of broiler chicks when oil extracted from thevetia seed was used as a substitute for palm oil in broiler diets.…”
Section: Chick Performancesupporting
confidence: 55%
“…The seed contains 60-65% oil while the defatted cake contains 30-53% protein (Steintz, 1962;Ibiyemi et al, 2002;Oluwaniyi et al, 2007) Documentation of the nutritive potentials of TS has been very scanty. Atteh et al (1990) investigated the replacement value of Thevetia oil for palm oil in broiler chicks' diets and recommended further processing of the oil prior to its being used effectively as a feed ingredient. Oderinde and Oladimeji (1990) analyzed the composition of the oil and indicated a total unsaturated fatty acids of 75.4% of which oleic acid was 31.46% and linoleic acid 43.90%.…”
Section: Introductionmentioning
confidence: 99%
“…Thevetia is grown as an ornamental plant. The oil has been shown to be a good alternative to palm oil in poultry diets (1). The utility or commercial potential of the oil, like other unsaturated oils, will depend on its thermal stability.…”
mentioning
confidence: 99%